21st anniversary of International Criminal Justice: reflections on the international criminal court and its relationship with the peruvian state - Rebaza Vilchez, Karen Maribel (2019)
July 17 is the world day of international criminal justice, marks the 21st anniversary of the adoption of the Rome Statute, the constituent instrument of the International Criminal Court (ICC), adopted at the "Diplomatic Conference of Plenipotentiaries of the United Nations on the establishment of an International Criminal Court".In this context, this article aims to reflect, from a legal-political perspective, on the importance of the ICC and the main challenges facing the Court, the international community and our country, in particular, in the fight against impunity.